Biomimetic Recognition and Optical Sensing of Carboxylic Acids in Water by Using a Buried Salt Bridge and the Hydrophobic Effect. (24th November 2020) - Huang, Xuan; Wang, Xiaoping; Quan, Mao; Yao, Huan; Ke, Hua; Jiang, Wei
Abstract: Buried salt bridges widely exist in protein structures but are rarely used in synthetic systems for molecular recognition in water. By mimicking the binding pocket of bioreceptors, we designed and synthesized a pair of endo ‐functionalized macrocyclic hosts with secondary ammonium groups in a hydrophobic cavity. We found that these macrocycles are able to selectively recognize carboxylic acids in water through salt bridges and the hydrophobic effect. Moreover, it was demonstrated that these macrocyclic receptors can be used in circular‐dichroism‐based optical chirality sensing of chiral carboxylic acids and fluorescent sensing of phenylpyruvic acid—a biomarker for phenylketonuria. This research showcases that buried salt bridges can be effectively used by endo ‐functionalized macrocyclic hosts for molecular recognition in water, where solvent screening on polar noncovalent interactions is high. Abstract : Buried salt bridges can be effectively used by a pair of endo ‐functionalized macrocyclic hosts for the selective recognition of functional carboxylic acids in water, where solvent screening on polar noncovalent interactions is high.